2001
DOI: 10.4269/ajtmh.2001.65.13
|View full text |Cite
|
Sign up to set email alerts
|

Short report: characterization of enteroaggregative Escherichia coli isolates from Iranian children.

Abstract: Abstract.We have previously shown that enteroaggregative Escherichia coli (EAEC) is an important pathogen among Iranian infants and children. To better understand the characteristics of EAEC in Iran, we analyzed EAEC isolates for the presence of pAA plasmid-borne factors. Ninety-eight E. coli strains that displayed the aggregative adherence (AA) pattern on HeLa cells were hybridized with the CVD432 (AA) probe and with genes encoding enteroaggregative heat-stable enterotoxin-1 and aggregative adherence fimbriae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…In that study, they suggested that the EAEC probe-positive strains might have a higher pathogenic potential or, alternatively, that EAEC probenegative strains may harbor virulence factors that have not yet been described. In contrast, Bouzari et al (3) found that EAEC probe-negative strains in Iran share virulence factors with EAEC probe-positive isolates. Our findings, along with those of Elias et al (7), suggest the possibility that EAEC probe-positive strains comprise a distinct subcategory of EAEC that could be called typical EAEC.…”
Section: Discussionmentioning
confidence: 96%
“…In that study, they suggested that the EAEC probe-positive strains might have a higher pathogenic potential or, alternatively, that EAEC probenegative strains may harbor virulence factors that have not yet been described. In contrast, Bouzari et al (3) found that EAEC probe-negative strains in Iran share virulence factors with EAEC probe-positive isolates. Our findings, along with those of Elias et al (7), suggest the possibility that EAEC probe-positive strains comprise a distinct subcategory of EAEC that could be called typical EAEC.…”
Section: Discussionmentioning
confidence: 96%
“…EAEC was discovered in 15.1% of cases in the diarrheal group and appeared to be the most prevalent pathogen among DEC categories. These cases seem to be the first EAEC infec- (3,4,12,24,36). The pathogenic mechanisms of EAEC infection are only partially understood and are most consistent with mucosal colonization followed by secretion of enterotoxins and cytotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular epidemiology may therefore be a useful tool for evaluating the pathogenicity of EAEC strains and has been used to identify the aafA gene, which encodes the structural subunit of AAF/II fimbriae, as a putative marker for potentially pathogenic strains (8,33). In this study, we employed strain collections obtained during case-control studies.…”
Section: Vol 42 2004 Iron Utilization In Eaec Strains 41mentioning
confidence: 99%